1992
DOI: 10.1172/jci115667
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-derived growth factor receptors on macrovascular endothelial cells mediate relaxation via nitric oxide in rat aorta.

Abstract: The effects ofplatelet-derived growth factor (PDGF) were studied in isolated rings of rat aorta contracted submaximally to phenylephrine. The BB isoform of PDGF elicited relaxation in rings with endothelium and further contraction in rings without endothelium. Both the endothelium-dependent relaxation and endothelium-independent contraction occurred at concentrations known to induce PDGF receptor-mediated responses in cultured cells. Furthermore, the relaxation was isoform specific. This conclusion is supporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 32 publications
2
17
0
Order By: Relevance
“…Most importantly, different PDGF ligands produce different cellular responses even when acting on a common receptor [140]. PDGF can stimulate mitogenesis in smooth muscle, NO-dependent vasorelaxation in endothelium-intact aortic rings [141], and microvascular angiogenesis in invasive breast cancer [142]. PDGF-BB can transform smooth muscle to a less contractile phenotype, and is crucial for proper lung development of neonatal rats [28, 143].…”
Section: Receptor Tyrosine Kinase-dependent Vasotrophic Factorsmentioning
confidence: 99%
“…Most importantly, different PDGF ligands produce different cellular responses even when acting on a common receptor [140]. PDGF can stimulate mitogenesis in smooth muscle, NO-dependent vasorelaxation in endothelium-intact aortic rings [141], and microvascular angiogenesis in invasive breast cancer [142]. PDGF-BB can transform smooth muscle to a less contractile phenotype, and is crucial for proper lung development of neonatal rats [28, 143].…”
Section: Receptor Tyrosine Kinase-dependent Vasotrophic Factorsmentioning
confidence: 99%
“…sphingosine-1-phosphate/EDG-1, and angiopoietin/Tie-2, have been shown to induce NO production. NO also has been shown to mediate downstream signaling, angiogenesis, and vascular SMC relaxation induced by these pathways (7,8,53). TGF-β1, which has been shown to mediate mural cell differentiation, also stimulates NO production through upregulation of eNOS transcription and stabilization of eNOS mRNA (54).…”
Section: Figurementioning
confidence: 99%
“…Early study showed that PDGF-BB can dilate rat aorta and mesenteric arteries. 26 However, we found that PDGF-AA impairs endothelium-dependent vasodilation. The difference may be caused by the differential expressions of PDGFRα and PDGFRβ in different vascular bed and different downstream signaling pathways.…”
Section: Discussionmentioning
confidence: 61%